Morphological behaviour of carbon/carbon and carbon/carbon-silicon carbide composites under reciprocating sliding conditions against uniphase and multiphase material - Kumar P.; Srivastava V.K. (My University, 2025)
The goal of this paper is to assess the variation in morphological behaviour of carbon/carbon and carbon/carbon-silicon carbide composite under reciprocating sliding against uniphase and multiphase substrates with variation of normal load. Chrome steel was chosen as uniphase and carbon/carbon and carbon/carbon-silicon carbide composites were slid in self and complementary mated pairs for multiphase materials. The worn surfaces were analysed under scanning electron microscope. Morphological study of worn surfaces showed that carbon/carbon composites slid against chrome steel did not show much abrasion whereas carbon/carbon-silicon carbide composites showed abrasion and, hard silicon carbide particles abraded the formed friction film. In self-mated pairs, carbon/carbon composites mainly showed delamination wear, and carbon/carbon-silicon carbide composites primarily showed matrix peeling and abrasion. In complementary mated pairs, carbon/carbon composites generated some wear debris with sharp edges. The abrasion and adhesion of carbon/carbon-silicon carbide composite were very less in case of complementary mated pair. Copyright © 2018 Inderscience Enterprises Ltd.